ACCELERATED IDIOVENTRICULAR RHYTHM: HISTORY OF RESEARCH - T. R. Treshkur; M. P. Chmelevsky; E. A. Tsurinova (Российский кардиологический журнал, 2015)
Accelerated idioventricular rhythm is a ventricular rhythm consisting of three or more consequent mono- or polymorphic complexes. It might be registered in patients with structural heart diseases, rarer in completely normal heart, might be found in sportsmen and children. Idioventricular rhythm might be seen in myocardial infarction, in reperfusion and under medications influence.The article focuses on the literature data that led to identification of this important ventricular arrhythmia.